2007
DOI: 10.1164/rccm.200605-704oc
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Atrophy and Hypertrophy Signaling in Patients with Chronic Obstructive Pulmonary Disease

Abstract: An increase in atrogin-1 and MuRF1 mRNA and FoxO-1 protein content was observed in the quadriceps of patients with COPD. The transcriptional regulation of atrogin-1 and MuRF1 may occur via FoxO-1, but independently of AKT. The overexpression of the muscle hypertrophic signaling pathways found in patients with COPD with muscle atrophy could represent an attempt to restore muscle mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
188
3
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 47 publications
17
188
3
6
Order By: Relevance
“…These results are interesting when compared with those of Doucet and colleagues (8). Probably, the differences between the present study and the report of Doucet et al (8) could be related to the different lung diseases and models assessed, since in the present study an asthmatic mouse model was studied, whereas Doucet et al (8) evaluated COPD disease in humans. The absence of molecular markers for muscle atrophy in the present OA group could be attributed to the short period (4 weeks) of the allergic sensitization protocol, which may not have been long enough to induce skeletal muscle atrophy.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…These results are interesting when compared with those of Doucet and colleagues (8). Probably, the differences between the present study and the report of Doucet et al (8) could be related to the different lung diseases and models assessed, since in the present study an asthmatic mouse model was studied, whereas Doucet et al (8) evaluated COPD disease in humans. The absence of molecular markers for muscle atrophy in the present OA group could be attributed to the short period (4 weeks) of the allergic sensitization protocol, which may not have been long enough to induce skeletal muscle atrophy.…”
Section: Discussioncontrasting
confidence: 42%
“…However, treadmill training reduced the expression of these genes in all exercised groups, a fact that could be beneficial in cachexia and disuse conditions. Recent studies have shown an increase of molecular markers of muscle atrophy in human COPD (8,9). Doucet and colleagues (8) reported an increase in the activation of muscle atrophy by the up-regulation of atrogin-1 and MuRF1 in the quadriceps muscle of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, systemic consequences may be secondary to the lung disease, probably via the release of inflammatory mediators/cytokines from the lung into the systemic circulation (6,10). Muscle wasting in COPD patients is probably one of the best known systemic features, and this may be due to the effects of cytokines from the lungs on skeletal muscle (11,12) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, limb muscle NF‐κB activity is increased in patients with lung cancer cachexia 41. FOXO mRNA and protein expression are increased in patients with COPD,38, 39, 42, 43, 44, 45 seemingly independent of body composition, although it is noticeable that in all studies, the patient group showed signs of emphysema. In the COPD patient group, FOXO‐1 protein expression was higher in limb muscles than in respiratory muscles, while this difference was not found in controls 46.…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 86%